Anticlastogenic effect of aqueous extracts of Agaricus blazei on CHO-k1 cells, studying different developmental phases of the mushroom - Bellini, M. F.; Giacomini, N. L.; Eira, A. F.; Ribeiro, L. R.; Mantovani, M. S. (Elsevier B.V., 2003)
The Agaricus blazei Murill (ABM) mushroom, known as the sun mushroom, is native to Brazil and has become known for its medicinal properties. This study examined the anticlastogenic effect of Agaricus blazei in Chinese hamster ovary cells, CHO-k1, by means of a chromosome aberration test using methyl methanesulphonate (MMS, 10(-4)M) as the DNA damage inducing agent. Two mushroom lines were used, ABM 99/26 and ABM 97/11, and the latter was used in the young (Y) and sporulating (S) developmental phases. The cells were treated for 12 h with MMS alone or combined with aqueous extracts of A. blazei at a final concentration of 0.15%, which were prepared at three different temperatures: (a) hot (60 degreesC), (b) room temperature (25 degreesC) and (c) chilled (4 degreesC). Mushroom extracts showed a marked anticlastogenic effect against DNA damage, as evidenced by a decrease in the number of cells with breaks, regardless of the line used, or the developmental stage or the temperature at which the extract was prepared. Generally, the extracts were more effective in reducing the isochromatid type breaks. The data obtained suggest that extracts of A. blazei mushroom are anticlastogenic under the conditions tested, mainly during the G1 and S stages of the cell cycle, where chromosome breaks of the isochromatid type are produced by the MMS agent. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei; CHO-k1 cells; chromosome aberration; mushroom; anticlastogenicity; cell culture